A new genus and species in the diatom family Eunotiaceae Kützing (Bacillariophyceae) from the Amazonian hydrographic region, Brazil - Burliga, Ana Luiza; Kociolekc, John Patrick; Salomoni, Saionara Eliane; Figueiredo, Daniela (Phytotaxa, 2013)
A new genus of the diatom family Eunotiaceae Kützing is described along with a new species. Eunotioforma Kociolek & Burliga gen. nov. shares asymmetry about the apical axis with other members of the family (except Peronia de Brébisson & Arnott ex Kitton ), and is distinguished from other genera in the family by having its raphe system almost entirely on the valve face and transapical striae interrupted near the center line of the valve. Eunotioforma mattogrossiana sp. nov. is described from the Do Sangue River, an oligotrophic and acidic stream situated in the State of Mato Grosso, Central Western region of Brazil. When compared with previously described taxa, the new species differs with respect to size, striae densities, areolar densities and an uncommonly high number of rimoportulae per valve. Seven other taxa are assigned to the new genus, and the systematic position of Eunotioforma and the evolution of the raphe within the family is discussed.